Perfectionism and perceptions of social loafing in competitive youth soccer - Vaartstra, M.; Dunn, J. G. H.; Dunn, J. C. (Journal of Sport Behavior, 2018)
Social loafing refers to the reduction in effort that occurs when an individual works collectively on a task compared to when working alone on a task (Karau & Williams, 1993; Latane, Williams, & Harkins, 1979). This reduction in individual effort has been shown to result in reduced (or sub-optimal) performance/productivity levels in a wide variety of achievement settings including (but not limited to) business/workplace teams, classroom tasks in academe, and physical/athletic performance tasks (for reviews see Hardy, 1990; Karau & Williams, 1993; Simms & Nichols, 2014). Understanding the impact of social loafing upon performance, the reasons why social loafing occurs, and methods by which social loafing can be reduced is particularly relevant in the context of interactive team sports (e.g., soccer, hockey, or basketball) where athletes trust and rely upon teammates to give maximum effort towards the achievement of team goals (both in training and competition). Even a small amount of social loafing in interactive team sports, especially at elite levels of competition, has the potential to jeopardize a team's chances of attaining competitive success (see Hardy, 1990; Hoigaard, Fuglestad, Peters, De Cuyper, De Backer, & Boen, 2010).